Pengaruh Stres Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Pt. Lancar Wiguna Sejahtera Area Jakarta Selatan - Bella Kurnia Putri; bella; Samcay, Samcay (Jurnal Sinergi Manajemen, 2024)
The aim of this research is to determine the positive and significant influence of work stress variables on employee performance, to determine the positive and significant influence of motivation variables on employee performance and to determine the positive and significant influence of work stress and motivation variablessimultaneously on employee performance at PT.lancar Wiguna Sejahtera. The sample used was a saturated sampling technique, totaling 70 employees. Data collection techniques through primary and secondary data. Data analysis techniques use descriptive statistics, validity test, reliability test, normality test,  multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysist test and f test.The research results show that: (1) Partially there is no positive and significant influence between work stress on employee performance at PT. Lancar Wiguna Sejahtera runs smoothly, this can be proven from the simple linear regression equation Y = 36.209+0.090 (2) Partially there is a opositive and significant influence between motivation on employee performance at PT. Lancar Wiguna Sejahtera's success, this can be proven from the simple linear regression equation Y = 27.928+0.294 (3) Simultaneously there is a positive and significant influence between work stress and motivation on employee performance at PT. Lancar Wiguna Sejahtera runs smoothly, this can be proven from the multiple linear regression equation Y = 27.016 + 0.045 X₁+ 0.277 ???????????? 3.129 with a significant level of 0.006 < 0 .05.